Dual self-organised shear banding behaviours and enhanced ductility in phase separating Zr-based bulk metallic glasses. Issue 19 (3rd July 2018) - Zhang, Z. Q.; Song, K. K.; Sun, B. A.; Wang, L.; Cui, W. C.; Qin, Y. S.; Han, X. L.; Xue, Q. S.; Peng, C. X.; Sarac, B.; Spieckermann, F.; Kaban, I.; et al.
Abstract: The multiplication and interaction of self-organised shear bands often transform to a stick-slip behaviour of a major shear band along the primary shear plane, and ultimately the major shear band becomes runaway and terminates the plasticity of bulk metallic glasses (BMGs). Here, we examined the deformation behaviours of the nanoscale phase-separating Zr65– x Cu25 Al10 Fe x ( x = 5 and 7.5 at.%) BMGs. The formation of multi-step phase separation, being mainly governed by nucleation and growth, results in the microstructural inhomogeneity on a wide range of length-scales and leads to obviously macroscopic and repeatable ductility. The good deformability can be attributed to two mechanisms for stabilizing shear banding process, i.e. the mutual interaction of multiple shear bands away from the major shear band and the delaying slip-to-failure of dense fine shear bands around the major shear band, both of which show a self-organised criticality yet with different power-law exponents. The two mechanisms could come into effect in the intermediate (stable) and later plastic deformation regime, respectively. Our findings provide a possibility to enhance the shear banding stability over the whole plastic deformation through a proper design of microstructure heterogeneities.